Effect Of Electrical Stimulation On Beef Quality - Sunil M (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 1993)
Application of electrical stimulation to pre-vigor muscle is considered as a method to prevent cold-shortening and to improve tenderness and consumer acceptability. The present study was conducted to evaluate the effect of electrical stimulation on changes in PH, non-protein nitrogen (NPN) content, Total viable count (TVC) and organoleptic characters of beef stored at ambient and refrigeration temperatures, at specified intervals of time. Ten carcasses of adult cattle were subjected to the study. Electrical stimulation (ES) (alternating current at 110V, 50Hz and 20 pulses per second) was applied on left fore-quarter for 120 seconds. The right fore-quarter was kept as control ( c) . Triceps brachii muscles were collected from ES and C sides immediately after stimulation and stored at ambient temperature for 12 h and at refrigeration temperature for 24h. The rate of fall in PH in ES was highly significant than in C at all intervals except at 24 h.The fall in PH in C was faster at ambient temperature compared to that under refrigeration temperature upto 8 h. Highly significant increase in NPN was observed during storage in ES compared to C. TVC was found to increase on storage at both temperatures. But the increase was significantly lower in ES than in C at ambient temperature at 8h. In refrigerated samples, at 12 h TVC in ES was lower than in C and the difference was significant (P<0.05). The organoleptic characters of samples were evaluated by a 5 member semi-trained taste panel. The flavor score for ES at ambient temperature was significantly higher than for C at 8h. The juiceness score was significantly higher in ES than in C at 0 and 8h at ambient temperature and at 24h at refrigeration temperature. Tenderness score at 8h was significantly higher in ES than in C at ambient temperature. Under refrigeration temperature difference in tenderness score between C and ES samples was highly significant at 8 and 24h. No significant difference was noticed in connective tissue score between C and ES samples. There was highly significant increase in overall acceptability for ES than for C at 8h at ambient temperature and 24h at refrigeration temperature.